In vivo assessment of the noradrenergic nucleus locus coeruleus in Alzheimer's disease and other types of dementia: Neuroimaging: Other neurodegenerative disorders. (7th December 2020) - Giorgi, Filippo Sean; Galgani, Alessandro; Lombardo, Francesco; Palermo, Giovanni; Hana, Hlavata; Daniele, Della Latta; Ghicopulos, Irene; Martini, Nicola; Baldacci, Filippo; Coi, Alessio; Tognoni, Gloria; Siciliano, Gabriele; et al.
Abstract: Background: The Locus Coeruleus (LC) is the main noradrenergic nucleus of the brain. Pathological analysis in humans have shown that LC is degenerated in Alzheimer's disease (AD), and that its impairment might start years before the occurrence of cognitive impairment. Several experimental studies in animal models even suggested a pathogenetic role of an early LC degeneration in AD pathogenesis. LC neuromelanin‐containing neurons can be assessed by using MRI scan, in T1‐weighted sequences. In this study, we assessed in vivo the integrity of LC by 3T MRI in patients with dementia due to AD (ADD) and in MCI subjects, comparing them with patients with Fronto‐temporal dementia (FTD), with patients with Lewy Body Dementia (LBD)/ Parkinson's Disease Dementia (PDD) and with healthy controls (HC). Method: 234 subjects (HC=60; MCI=80; ADD=40; FTD=18; LBD/PDD=36) were submitted to a 3 Tesla brain MRI (Signa‐GEH), including neuromelanin (NM)‐sensitive FSE T1‐weighted sequences for LC study. The sequences were then evaluated using a semi‐automatic software by blinded operators. An indirect measures of LC volume, based on the number of Voxels selected, is expressed by the parameter VOX. All subjects underwent detailed clinical and neuropsychological assessment. Result: VOX was significantly lower in ADD compared to HC, while no differences were observed between HC and FTD. The lowest values of were observed in LBD/PDD and Early Onset AD (EOAD) patients. MCI subjects showed an LC signal lower than HC, although not statistically significant. Patients with confirmed AD pathology presented lower values of VOX than HC, and their cognitive performances correlated with the degree of LC signal reduction. Conclusion: We observed in vivo a marked alteration of LC signal in AD patients, compared to healthy controls, in line with the hypothesis of LC involvement in AD pathogenesis; the severe alteration found in EOAD, further supports this association. As expected from neuropathological and NM‐MRI studies, also PDD/LBD showed LC alterations, while FTD did not. In MCI a trend was observed, even if not significant: a longitudinal study is required to evaluate potential association with ADD conversion rate. Funding sponsor: Ministero della Salute PE‐2013‐02359574 (P.I.: FSG).